REPETITIVE MCKENZIE SPINAL EXTENSION EXERCISES ON CARDIOVASCULAR RESPONSES IN CLASS I OBESE SUBJECTS (International Journal of Physiotherapy, 2016)
Background: Obese population is dramatically increasing worldwide. There is a strong association between obesity and low back pain. The 1-month prevalence of low back pain ranges from 30% to 40% in the general population. McKenzie method is commonly used in the diagnosis and management of patients with back pain. The objective of the study is to examine the cardiovascular responses of two common exercises namely, extension in lying (EIL) and extension in standing (EIS) used in the McKenzie system with different repetitions among class I obese subjects.Method: 50 class I obese subjects (25 males and 25 females) were randomly selected within the age range of 20-40 years. Baseline measures of resting heart rate (HR), blood pressure (BP) and rate pressure product (RPP) were taken before and after exercises. Multiple comparisons were done to analyze the significance within groups. One-way analysis of variance for repeated measures was used to compare the dependent values obtained at rest and after 10, 15 and 20 repetitions. Independent “t” test was used to determine the significance between groups.Results: No significant differences (p>0.05) were found in SBP and DBP after 10 repetitions in group 1 and among HR and SBP after 10 and 15 repetitions in group 2. There was a significant difference (p